Renal artery in tufted capuchin monkey: Structure and morphometry - De Mello, Josiane Medeiros; Orsi, Antonio Marcos [UNESP]; Gomes, Célia Regina De Godoy; Spilla, Caio Sérgio Galina; De Oliveira, José Américo; Torrejais, Marcia Miranda; Billoti, Carolina Correia (Universidade Estadual de Maringa, 2018)
The objective was to describe the structure of the renal artery in capuchin monkey at the level of the proximal and distal arterial segments. Morphometric analysis was performed referring to the thickness and quantification of tissue elements of the renal artery tunica media in both segments. Renal arteries of eight adult capuchin monkeys were collected for histological analysis of the two segments, being the proximal part branched from the abdominal aorta, and the distal part localized next to the renal hilus. The quantification of smooth muscle cells and connective elements was carried out in transversal sections of the two segments; for the tunica media, it was used the volume densities of smooth muscle cells, collagen and elastic fibers. Considering these volume densities obtained for each segment, it was verified that the proximal segment showed a marked myoconnective architecture, while the distal segment was characterized by a single muscular artery. Apparently, the mixed architecture of the proximal segment could be related to a blood flow control at the aortic emergence of the renal artery, which helped to guarantee a priority flow of enriched plasma into the kidney parenchyma.
Artéria renal do macaco prego: Estrutura e morfometria
Keywords: Anatomy and histology; Blood vessels; Mammals